Exploring Health Care Providers' Perceptions of the Needs of Stroke Carers: Informing Development of an Optimal Health Program. Issue 5 (September 2014) - O'Brien, Casey L.; Moore, Gaye; Rolley, John X.; Ski, Chantal F.; Thompson, David R.; Lautenschlager, Nicola T.; Gonzales, Graeme; Hsueh, Ya-seng (Arthur); Castle, David
Abstract : Background: Health care provider experiences of the carer have been researched, but little is written about how these can inform development of support programs.Objectives: This study aimed to (1) explore health care provider perceptions of stroke carer roles and support needs and (2) examine carer needs across the stroke care trajectory to assist with development of an Optimal Health Program (OHP) to support carers. This study is part of a staged program of research that will evaluate and refine the OHP.Methods: Four dual-moderated semi-structured focus groups of stroke health care providers across acute, subacute, and community rehabilitation services were conducted. Facilitators used a semi-structured focus group schedule to guide discussion. Sessions were recorded, transcribed, and analyzed using thematic and content analysis.Results: Three key themes emerged: transition, information, and impact of stroke. A number of subthemes highlighted the distinct roles of health care providers and carers. Specific elements of the OHP were identified as having the potential to advance support for carers across the stroke care trajectory.Discussion: Findings support the integration of an OHP for carers within existing stroke care services in Australian public hospital and community settings.Conclusion: This study suggests how health care provider experiences could inform a self-management OHP to assist carers in navigating stroke services and to address their health-related concerns.